2019
DOI: 10.1111/jfbc.13074
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and bioactivities of compounds from Fuscoporia torulosa mushroom

Abstract: Chromatographic purification of Fuscoporia torulosa extracts resulted in the isolation and characterization of a new steroid, 5α,8α‐epidioxyergosta‐6,22‐dien‐3β‐il‐palmitate (1) and 10 known compounds (2–11). The structures of compounds were elucidated by IR, NMR, MS analyses, and comparison with literature data. Cytotoxic activities against MCF‐7 (breast cancer), PC‐3 (prostate cancer), and 3T3 (nontumor) of the extracts and cytotoxic, antioxidant, cholinesterase, and tyrosinase inhibitory activities of all i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…In 2018, Zhang and colleagues reported that polysaccharides derived from Flammulina velutipes had various pharmacological effects, including AChEi activity [171]. In 2019, Deveci and colleagues reported that a polysaccharide obtained from Pleurotus ostreatus, a mushroom tree, exhibited significant inhibitory activity against BChE [172]. Badshah and colleagues reported that polysaccharides isolated from a wide range of mushrooms, which contain glucans, krestin, and lentinan, have significant AChE and BChE inhibitory activity and are being regarded as novel drug therapies for the management of AD and PD [173,174].…”
Section: Anticholinesterase Activity Of Polysaccharidesmentioning
confidence: 99%
“…In 2018, Zhang and colleagues reported that polysaccharides derived from Flammulina velutipes had various pharmacological effects, including AChEi activity [171]. In 2019, Deveci and colleagues reported that a polysaccharide obtained from Pleurotus ostreatus, a mushroom tree, exhibited significant inhibitory activity against BChE [172]. Badshah and colleagues reported that polysaccharides isolated from a wide range of mushrooms, which contain glucans, krestin, and lentinan, have significant AChE and BChE inhibitory activity and are being regarded as novel drug therapies for the management of AD and PD [173,174].…”
Section: Anticholinesterase Activity Of Polysaccharidesmentioning
confidence: 99%
“…In the same context, Deveci et al [ 6 ], reported the isolation of a new steroid 5α,8α-epidioxyergosta‐6,22‐dien‐3β‐il‐palmitate, along with ten known compounds with a weak profile of inhibition, with inhibition percentages below 15% at 100 μg/mL doses. Thus, it can explain the fact that steroids present a poor inhibition profile as demonstrated for the null effect observed for the remaining isolated compounds against AChE.…”
Section: Resultsmentioning
confidence: 99%
“…Fractionation of the methanolic extract of F. torulosa revealed the presence of 5α,8αepidioxyergosta-6,22-dien-3β-il-palmitate and ten compounds (compounds 2 to 11). The methanolic extract and one of the compounds, compound 8, exhibited indicated high inhibitory potency against MCF-7 cells and butyrylcholinesterase (Deveci et al 2019).…”
Section: Fuscoporia Torulosamentioning
confidence: 99%